Nel nome di Elais: dall’olio di oliva agli oli essenziali - Donnoli, Maria Irene; Smaldone, Dina Anna Maria (Chimica nella Scuola, 2025)
This work represents an educational experience included in the PTOF project named “The essential is circular”, which involves extraction of essential oils by natural sources like lavender, rosemary, orange, other citrus fruits and other materials. Most of these sources are partly used for other processes and the unused portion most often constitutes waste. The idea is to turn these potential wastes into resources by implementing the concept of circular economy; in this experience the students develop specific skills using the teaching methodology of Service Learning.